2011
DOI: 10.1177/1475090211402288
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurement of the surface velocity field in an externally induced sloshing tank

Abstract: In this work, the unsteady free-surface velocities during the surge motion of a liquid tank are determined through experimental investigation. A new experimental approach has been discussed for capturing the free surface of the liquid during tank excitation. In order to avoid violent motion in the tank, the tank is excited with a low frequency (up to 47 per cent of the first-mode frequency) which leads to low-steepness waves in the container. When a container oscillates at a low excitation frequency, the wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This phenomenon is in accordance with the basic law of structural dynamics. Figure 4 presents a comparison of the theoretical and experimental values of o 2 1 l=g, in which the experimental results are from [21][22][23][24]. In Figure 4, it can be seen that the theoretical and experimental values are in very close agreement.…”
Section: Fitting Expression Of the First Sloshing Frequencymentioning
confidence: 81%
“…This phenomenon is in accordance with the basic law of structural dynamics. Figure 4 presents a comparison of the theoretical and experimental values of o 2 1 l=g, in which the experimental results are from [21][22][23][24]. In Figure 4, it can be seen that the theoretical and experimental values are in very close agreement.…”
Section: Fitting Expression Of the First Sloshing Frequencymentioning
confidence: 81%
“…Liquid storage tanks must be fabricated using transparent materials to use PIV and PTV, which have been widely used to measure the water level responses of fluids. Inputting special particles in the tanks must be possible and the particles must be illuminated with a laser beam [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Several contributions have recently demonstrated that it is possible to measure the free surface velocity with the high resolution and capture rate that is typical of Particle Image Velocimetry (PIV), see Weitbrecht et al (2002); Meselhe et al (2004); Sokoray-Varga and Józsa (2008); Eswaran et al (2011) for hydraulics applications and Berger and Corrsin (1974);Heining et al (2012); Landel et al (2015) for liquid film applications.…”
Section: Introductionmentioning
confidence: 99%